GE_GERICHTE C/5883/2018 vom 28. September 2018 - GE Cour de justice (2018)
MAINLEVÉE DÉFINITIVE ; CESSION DE CRÉANCE(CO) ; RECOUVREMENT ; FICTION DE LA NOTIFICATION ; TUTELLE | CPC.138.al3; CPC.326; LP.80.al1; LARPA.2; Cst.29.al2